Dynamics Modeling and Response Analysis of Gear-screw Actuators of Tiltrotor Aircrafts - Wang Cheng; Li Zhengminqing; Sheng Wei; Pan Dongling (Jixie chuandong)
The tilting mechanism of a tiltrotor aircraft is a complex structure comprised of gear pairs and ball screw pairs, with its dynamic challenges being particularly prominent. To precisely analyze its dynamic behavior and uncover the vibration mechanism, a dynamic coupling modeling method for a gear-ball screw actuator system was proposed. In this method, the impact excitation from the ball screw pair and the quasi-static transmission errors from the gear pair were considered. By solving the eigenvalue problem based on the system's dynamic equations, the natural frequencies and modes were determined. A comparison with the finite element modal analysis results confirmed the accuracy of the theoretical model. On this basis, an analysis of the dynamic behavior of the gear-ball screw actuator system was conducted, along with an exploration of the influence of structural parameters of the ball screw pairs on the output response. The results show that the axial vibration response of the ball screw decreases with an increase in the helix angle, while it follows a trend of initial increase followed by decrease with an increase in the contact angle.